The Influence of Perceived Organizational Support on Organizational Citizenship Behavior with Organizational Commitment as a Mediating Variable (Study on Nook Restaurant Bali Employees) - Gede Rio Selwy Ferdinan; I Gusti Ayu Manuati Dewi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Successful organizations need employees who will go beyond their formal duties and are willing to deliver performance that exceeds expectations. The purpose of this research is to explain the influence of perceived organizational support on organizational citizenship behavior with organizational commitment as a mediating variable in NOOK restaurant Bali employees. The theory used in this research is Social Exchange Theory. The sample in this study amounted to 90 people who were determined using saturated sampling techniques. Data was collected through distributing a Google Form questionnaire using the SMART PLS 3.0 model data analysis technique. The results of this research show that perceived organizational support has a positive and significant effect on organizational citizenship behavior, perceived organizational support has a positive and significant effect on organizational commitment, organizational commitment has a positive and significant effect on organizational citizenship behavior, and organizational commitment is able to mediate the effect of perceived organizational support on organizational citizenship behavior. It is hoped that the results of this research can be used as consideration and input for restaurant management in making policies to improve organizational citizenship behavior.